The determinants of commercial bank's performance in Malaysia / Sh Nurnajihah Nurintan Sh Asli - Sh Asli, Sh Nurnajihah Nurintan (2019)
This paper studied the factor affecting performance of the commercial banks that influence variables bank-specific factors on selected bank profitability in Malaysia during the period 2014-2018. Panel data which consist of 10 selected banks in Malaysia which is local bank and foreign bank been used in this study. Bank return on assets (ROA) has been used as an instrument to measure bank profitability. Bank specific variable that used in this study included capital ratio (CAP), Bank Size (BS) and Liquidity (LIQ). In order to study about this topic, the researcher obtained secondary data from World Bank, Mendeley and annual report of each bank. Fixed effect model was chosen to examine the effect of bank specific factors toward bank profitability. The researchers found that all the independents variables have positive relationship with bank profitability except liquidity. Other than this, capital ratio and bank size is significant to affect bank profitability while this factor are critical components in influencing profitability of the commercial bank in Malaysia.